The Effects of a Brief Mindfulness Intervention on Lab-based Aggression - Seavey, Amanda Eliza (2014)
Aggression and violence are severe and prevalent problems associated with numerous negative health consequences and increased health care costs. Prevalence rates vary with the highest rates being among young adult populations. Some research indicates that aggression perpetration is an attempt at controlling negative affect. Therefore, many have posited that emotion regulation may be an amenable risk factor for violence and aggression, and interventions such as mindfulness-based therapies designed to enhance emotion regulation and distress tolerance may be helpful. Previous research has found positive effects on psychological well-being using even brief mindfulness interventions. Thus, the current study aimed to investigate how a brief mindfulness intervention affects aggressive responding among 97 college students. Participants completed measures of general aggression and mindfulness. Participants were randomly assigned to receive a brief mindfulness intervention (or no intervention), followed by completion of a 25-minute lab-based aggression exercise in which participants ostensibly competed against an opponent to earn money via button-pressing. Participants then completed a measure of state mindfulness as a manipulation check. Hypotheses that participants in the mindfulness intervention group would respond less aggressively than those in the control group even after controlling for trait mindfulness and previous aggression were not supported. Results indicated that groups did not differ on state mindfulness or aggression. Future research should improve upon the current study by addressing methodological concerns with the mindfulness task in order to better understand the relationship between mindfulness and aggression